Dealing with doctoral students: Tips from the trenches - Erwee, R; Albion, P; van Rensburg, H; Malan, R (South African Journal of Higher Education, 2011)
To enhance research into revitalising supervisory practices, the aim of this study is to identify approaches of supervisors to mentoring and facilitating doctoral students’ progress. Scenarios were created to describe typical situations that supervisors face, namely non-responsive students, dealing with students with low English language proficiency, high workloads of supervisors, managing conflicting expectations about the level of support and implementing high presence technologies. Interviews were conducted with supervisors in two faculties at an Australian university. These supervisors displayed unique insights about their underlying value systems in approaching challenging students and situations. One of the key issues is understanding the contexts of students and supervisors and determining the best way to communicate on the basis of this understanding. The study generated improved guidelines for supervisors on how to deal with doctoral students’ expectations as well as how to use online learning tools more effectively to deliver services to doctoral students.